Ethnoscience Studies on The Malamang Tradition in Sub-District VII Koto Sungai Sarik Nagari as A Source of Science Learning in Junior High School - Syafira, Annisa; Syarif, Muhammad Ilham (Journal of Indonesian Science Teachers, 2025)
The purpose of this study is to study the ethnoscience aspect of the Malamang tradition in VII Koto Sungai Sarik Nagari District, Pariaman as a science learning material for junior high school/Islamic junior high school students. This study is a study conducted using a case study method by conducting observations and interviews. The results of this research indicate that in the Malamang culture, there is a significant relationship with science learning in junior high schools/Islamic junior high schools, especially in the material of Temperature and Heat as subject matter. This study can be a reference in learning Natural Sciences in Schools.